2010
DOI: 10.1002/ajpa.21246
|View full text |Cite
|
Sign up to set email alerts
|

Brief communication: Allelic and haplotypic structure at the DRD2 locus among five North Indian caste populations

Abstract: The dopamine D2 receptor (DRD2) gene, with its known human-specific derived alleles that can facilitate haplotype reconstruction, presents an important locus for anthropological studies. The three sites (TaqIA, TaqIB, and TaqID) of the DRD2 gene are widely studied in various world populations. However, no work has been previously published on DRD2 gene polymorphisms among North Indian populations. Thus, the present study attempts to understand the genetic structure of North Indian upper caste populations using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
5
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
6
5
1
Order By: Relevance
“…However, the present findings are in agreement with the proposal of the peopling of Manipur through China (Pemberton, 1835). The North to South decrease of N haplogroup frequencies in the populations studied herein, with the lowest frequency being documented among Dravidian and AustroAsiatic populations, reflects the extent of admixture, which is decreasing from North India to South India as was also reported by previous studies (Reich et al, 2009;Saraswathy et al, 2010). B haplogroup is found to be absent among the Siberian populations (Kolman et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
“…However, the present findings are in agreement with the proposal of the peopling of Manipur through China (Pemberton, 1835). The North to South decrease of N haplogroup frequencies in the populations studied herein, with the lowest frequency being documented among Dravidian and AustroAsiatic populations, reflects the extent of admixture, which is decreasing from North India to South India as was also reported by previous studies (Reich et al, 2009;Saraswathy et al, 2010). B haplogroup is found to be absent among the Siberian populations (Kolman et al, 1996).…”
Section: Discussionsupporting
confidence: 81%
“…This hypothesis is further confirmed based on limited sequence data reported for primate DRD4 4R allele (Livak et al, 1995), the lower level of linkage disequilibrium (LD) for polymorphisms surrounding this allele, and the sequence motif arrangements of the non-4R alleles (Ding et al, 2002). The presence of the human ancestral 4R allele at significant frequencies in all Indian populations, irrespective of their tribe and caste status, supports the common genetic substratum of the Indian population proposed previously (Saraswathy et al, 2010). Moreover, the high frequency of progenitor 4R allele among the south Indian and east Indian populations belonging to Proto-Australoid ethnic elements and Dravidian and Austro-Asiatic speakers, respectively, is strongly supportive of the view that Proto-Austaloid groups were the earliest settlers in India and might have diversified into two groups in the course of human evolution in the region (Kumar et al, 2008).…”
Section: Discussionsupporting
confidence: 78%
“…Evidence of fossilized Hominoidae (Pongidae and Protohominidae) of late Miocene period, such as Gigantopithecus, Brahmapithecus, Ramapithecus, Sivapithecus from Siwaliks and Homo erectus from the Narmada basin of India, hints towards the role of the subcontinent in the origin of human species (Pilbeam, 1979;Benefit and McCrossin, 1995;Ruvolo, 1997;Trinkaus, 2005). This can be further supported by a recent report by Saraswathy et al (2010), which proposed a common genetic substratum of India. To understand the peopling of India, and in turn the peopling of the world, researchers have used several genetic markers.…”
Section: Introductionmentioning
confidence: 57%
“…Here in the same population (but in north India), we found the mean average heterozygosity of 0.33 (standard deviation of AE 0.1786) for all the 14 markers, and this moderately low heterozygosity among Aggarwal population clearly supports Reich et al (2009) for the founder events of the Vysya population of south India. Saraswathy et al (2010) studied the same population for the DRD2 locus and found a similar average heterozygosity of 0.381. Finally, our clan-based stratified analysis on the basis of Breslow-Day test for homogeneity of odds ratio clearly provides empirical evidence that the Aggarwal is a homogenous population group and is not genetically stratified on the basis of its existing clans (Table 2).…”
Section: Resultsmentioning
confidence: 82%